Features of noninvasive cerebral oximetry and central hemodynamics in young children with hydrocephalus - O.S. Pavlysh; V.I. Snisar (Medičnì Perspektivi)
Hydrocephalus is one of the most common diseases of the nervous system in young children. Features of structural and morphological changes of the brain in children with hydrocephalus are the predominance of signs of periventricular ischemia of brain tissue due to cerebral circulatory disorders. Despite the existence of a large number of methods for assessing cerebral hemodynamics, in the modern literature there is only limited information about the oxygen status of the brain when using different types of anesthesia in children. The aim of the study was to assess the dynamics of noninvasive cerebral oximetry and central hemodynamics in young children with hydrocephalus during ventriculoperitoneal shunting. The research included 59 young children with acquired hydrocephalus who underwent ventriculoperitoneal shunting. 34 children underwent total intravenous anesthesia with propofol, 25 children – total inhalation anesthesia with sevoflurane. Intraoperative control of vital functions of the patient was performed: systolic blood pressure, diastolic blood pressure, mean arterial pressure, heart rate, regional saturation, carbon dioxide level on exhalation, sevoflurane concentration on inspiration and exhalation, non-invasive cerebral indicators. Children with acquired hydrocephalus had cerebral oximetry within normal regional level. The use of sevoflurane leads to increased cerebral oxygenation by inhibiting cerebral metabolic needs for oxygen and vasodilation of blood vessels with increased cerebral blood flow. Total intravenous anesthesia does not change the rate of intraoperative cerebral oxygenation, leads to hemodynamic changes in the form of decreased stroke volume, which may indicate that propofol reduces the level of oxygen consumption by the brain with decreased cerebral blood flow against the background of hemodynamic inhibition.